Public Health Financing, Remittances, and Inclusive Growth in Resource-rich Countries: Evidence from Nigeria and Mozambique - Sunday Osahon Igbinedion; Favoured Mogbolu (Jurnal Ekonomi dan Studi Pembangunan, 2023)
The persistent challenge of accelerating economic growth via government health expenditure has been widely acknowledged in extant literature. Though such government expenditures have impacted growth in some cases, but the desire to further stimulate growth has brought about the need to explore more options in that regard. Interestingly, remittance has evolved over time as an alternative. Yet, the relative impact of these two covariates in promoting inclusive growth in natural resource rich countries remains understudied in Africa.The study therefore examines the relative impact of both government health expenditure and personal remittances received on inclusive growth in the two resource-rich countries of Nigeria and Mozambique. Utilizing the Fully Modified Ordinary Least Square Method (FMOLS) and the error correction mechanism on time series data for each of the two countries, the results revealed that economic fundamentals like government health expenditure, personal remittances received, and per capita income are of considerable significance in the task of enthroning inclusive growth in theresource-rich countries of Nigeria and Mozambique.